2010
DOI: 10.1063/1.3456175
|View full text |Cite
|
Sign up to set email alerts
|

Silicon based microfluidic cell for terahertz frequencies

Abstract: We present a detailed analysis of the design, fabrication and testing of a silicon based, microfluidic cell, for transmission terahertz time-domain spectroscopy. The sensitivity of the device is tested through a range of experiments involving primary alcohol/water mixtures. The dielectric properties of these solutions are subsequently extracted using a Nelder–Mead search algorithm, and are in good agreement with literature values obtained via alternative techniques. Quantities in the order of 2 μmol can be eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…76 In addition, microfluidic devices for liquid spectroscopy have also been demonstrated. 77 As soon as other molecules, such as carbohydrates or proteins, are dissolved in water, it is possible to distinguish between different populations of water molecules based on the change in the relaxational dynamics because the water molecules that are part of the solvation shell exhibit a significantly different dynamics than the bulk water molecules. This concept was applied to study a wide range of molecular interactions of biomolecules during solvation: lactose; 78 threhalose, lactose, and glucose; 79 among others.…”
Section: Mesoscopic Structure and Dynamicsmentioning
confidence: 99%
“…76 In addition, microfluidic devices for liquid spectroscopy have also been demonstrated. 77 As soon as other molecules, such as carbohydrates or proteins, are dissolved in water, it is possible to distinguish between different populations of water molecules based on the change in the relaxational dynamics because the water molecules that are part of the solvation shell exhibit a significantly different dynamics than the bulk water molecules. This concept was applied to study a wide range of molecular interactions of biomolecules during solvation: lactose; 78 threhalose, lactose, and glucose; 79 among others.…”
Section: Mesoscopic Structure and Dynamicsmentioning
confidence: 99%
“…This is extremely critical for sensing of biological molecules in aqueous solution, since THz absorption by water is significantly large and has been a challenge to THz spectroscopy for biological sensing. 34 Earlier reports using the THz metamaterial for sensing of sugars, 35 yeast, 36 virus, 37,38 and other biomaterials 39,40 have been carried out under dehydrated conditions. 41 Few studies have demonstrated sensing with THz metamaterial in aqueous environment by confining aqueous solution at the microscale level.…”
mentioning
confidence: 99%
“…41 Few studies have demonstrated sensing with THz metamaterial in aqueous environment by confining aqueous solution at the microscale level. 34,[42][43][44][45] However, further reduction of the analyte volume to the nanoscale level would aid in much higher sensitivity of detection as the absorption from water could be greatly reduced. More interestingly, confinement of liquid in extremely small space also allows for efficient delivery of molecules to the sensing area, and the recent effort in the field of microfluidics has scaled down the interaction space to nanometer size.…”
mentioning
confidence: 99%
“…Free-space THz measurements typically employ a transmission geometry, using a suitably thin sample cell to minimise attenuation [2]. However, the closely-spaced material interfaces of the cell introduce etalons into the measured time-domain signal, arising from interfacial reflections, which can adversely affect subsequent data analysis.…”
Section: Introductionmentioning
confidence: 99%